OPTIMISING THE IVIG SERVICE: AN AUDIT OF MONITORING AND DOSAGE. Issue 12 (15th November 2016) - Sarr-Gonzales, Scherezade; Zarkali, Angeliki; Bonifacio, Guendalina; Englezou, Christina; Manji, Hadi; Parton, Matt; Hanna, Mike; Lunn, Mike; Reilly, Mary; Carr, Aisling
Abstract : Background: In NHNN, 388 patients received 203, 571 g of IVIG (£35/g) during 2014/15 amounting to 3127 patient days (£250/person/day). The majority of the 91.7% on long-term treatment are neuromuscular patients. Aims: In 2011 the Department of Health updated guidelines for monitoring and dosing of IVIg. This is an audit of a new, consultant-led IVIg monitoring service, run as a weekly outpatient clinic from July 2015. Methods: We prospectively documented achievement of DOH recommendations on monitoring, patient outcome and any dosing changes. Comparison was made with the preceding year Results: 90 neuromuscular IVIg patients (60% male) were referred. 58.9% CIDP, 35.6% MMN, 4% myositis, 2.5% other. Proportion assessed annually improved from 89.7% to 100%. Appropriate reporting to pharmacy/national IVIg database improved from 35% to 100%. Usage of established outcome measures improved from 2.5 to 3.4 per patient. A reduction of 472 g/month (4 treatment cessations) and 6 treatment days/month was achieved (£18, 020/month cost reduction) in the first 6 months. Mean (S.E.) interim improvement in RODS score=+2.2 (0.4); 10 m timed walk =+1.5 (2.1) and MRC sum score=+0.9 (1.1) indicating treatment responsiveness. Conclusion: The new service has optimised compliance with national guidelines and facilitated safe, stable reduction in dose and treatment days.